Differential Physiological and Molecular Processes in the Root May Underlie Contrasting Salt Tolerance in Two Egyptian Rice Cultivars at the Seedling Stage - Ahmad Mohammad M. Mekawy; Dekoum V.M. Assaha; Jiacheng Li; Asmaa Yusuf; Doaa Mostafa; Mahmoud Ali Shoulkamy; Akihiro Ueda (Journal of Soil Science and Plant Nutrition, 2024)
This study aimed to compare various responses of two Egyptian rice accessions bred for high yields, Sakha108 and Giza177, to salt stress at the seedling stage. Twenty-eight-day-old seedlings of two cultivars were grown in a hydroponic medium under control conditions (no NaCl) and salt stress (75 mM NaCl) for 12 days. Growth (dry weight), Na + and K + concentrations, enzymatic and non-enzymatic antioxidants, malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and expression of Na + and K + transport-coding genes were recorded. Sakha108’s growth (18% rise from control) was significantly higher than Giza177’s. Both cultivars accumulated similar amounts of Na + in the leaves and sheaths, however, Sakha108 had higher Na + concentrations in the roots than Giza177 (13.3% higher). Root K + concentration dropped dramatically (~ 2-fold reduction) in Giza177 roots while remaining unchanged in Sakha108 roots. The concentrations of H 2 O 2 (root) and MDA (leaf and root) were higher in Giza177 than in Sakha108, although the difference was not statistically significant. Proline and total flavonoid (TF) contents in Sakha108 roots were greater than those in Giza177 roots. The expression of OsHKT1;5 and OsHKT2;1 genes declined in both cultivars, whereas expressions of OsSOS1 , OsNHX1 , and OsHAK7 were induced in Sakha108 but, except for OsHAK7 , were repressed in Giza177. Combined, these findings suggest that Sakha108 is more resistant to salt stress than Giza177 is, and that this variation in tolerance may have its origins in the root systems of the two cultivars. Thus, these adaptive traits in the root of Sakha 108 could be explored for engineering stress tolerance in susceptible but high-yielding rice cultivars.